Lebesgue-type Inequality for Orthogonal Matching Pursuit for Micro-coherent Dictionaries - Ye Peixin; Wei Xiujie (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In this paper, we investigate the efficiency of some kind of Greedy Algorithms with respect to dictionaries from Hilbert spaces. We establish ideal Lebesgue-type inequality for Orthogonal Matching Pursuit also known in literature as the Orthogonal Greedy Algorithm for -coherent dictionaries. We show that the Orthogonal Matching Pursuit provides an almost optimal approximation on the first. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1890